Implementasi Supervisi Akademik dalam Peningkatan Kemampuan Guru SMA Swasta Raudhatul Fuqara Aceh Utara - Musdar, Musdar; Wardhani, Nia (Pase: Journal of Contemporary Islamic Education, 2022)
One of the managerial functions in educational institutions is academic supervision. This is to improve teachers' abilities in teaching and learning activities and managing learning in the classroom and outside the classroom. The purpose of this research is to obtain information about the implementation of academic supervision carried out by school principals in order to improve teacher performance. This study uses a qualitative method. Data collection was carried out through interviews, observation, and documentation studies. The subjects of this study were the principals and teachers of Raudhatul Fuqara Private High School, North Aceh. The results of the research show that the implementation of academic supervision is carried out in three stages: 1) planning; by determining the objectives and making a supervision schedule, 2) implementation; by carrying out supervision outside the classroom and supervision in the classroom, 3) evaluation; by carrying out data collection, assessment, detection of weaknesses, repairing weaknesses, guidance, and development.